Association of the central venous-to-arterial carbon dioxide difference with low cardiac output-related outcomes after cardiac surgery in children: a prospective cohort study - Chaiwiriyawong, Pornnicha; Jarutach, Jirayut; Saelim, Kantara; Duangpakdee, Pongsanae; Vichitkunakorn, Polathep; Prasertsan, Pharsai (Frontiers in Pediatrics, 2025)
IntroductionLow-cardiac-output syndrome (LCOS) after cardiac surgery may lead to poor postoperative outcomes. The venous-to-arterial carbon dioxide partial pressure difference (VACO2) showed association with poor outcomes in adults with cardiac surgery, but it's validity in pediatric population is uncertain. We evaluated the association of VACO2 with LCOS-related outcomes and the correlation with other surrogate markers such as lactate levels and oxygen extraction ratio.MethodsThis prospective cohort study was conducted at an intensive care unit in a tertiary academic hospital. Children aged 1 day–18 years old undergoing elective cardiac surgery with cardiopulmonary bypass between August 2021 and December 2023 were included. Arterial and venous blood gases were collected at intensive care unit admission and at 6, 12, and 24 h postoperatively. The LCOS-related outcomes were defined as at least two of the following criteria being met within 24 h postoperatively: vasopressor-inotropic score ≥20, ejection fraction <50% on echocardiography, need for serious post-operative intervention, and death.ResultsOf the 127 included patients (median age: 44.4 months), 37 (29.1%) had a Risk Adjustment for Congenital Heart Surgery score ≥3, and 26 (20.4%) had LCOS-related outcomes. Linear mixed model regression analysis revealed that the VACO2 did not significantly differ between patients with and without LCOS-related outcomes at all four time points. VACO2 showed a fair-to-weak correlation with the oxygen extraction ratio (R2 = 0.58; p < 0.001, R2 = 0.22; p = 0.015, and R2 = 0.19; p = 0.045, at 6, 12, and 24 h postoperatively, respectively) but showed no correlation with lactate levels. A persistently high VACO2 (≥6 mmHg) at 6 h postoperatively was significantly associated with fewer 28-day inotrope-free and intensive care unit-free days.DiscussionVACO2 was not significantly associated with LCOS-related outcomes in children after cardiac surgery with cardiopulmonary bypass. A persistently high VACO2 at 6 h postoperatively was correlated with prolonged inotrope use and a prolonged intensive care unit stay.